The Relationship Between Teacher Quality and Secondary School Students’ Performance in Biology Concept of Genetics - Akachukwu, Esther Ebele; Mbaegbu, Chioma Stephane (Teaching, Learning, and Development, 2026)
This study investigated the relationship between teacher quality and secondary school students’ performance in Biology concept of genetics in Onitsha Education zone. Two purposes of study, two research questions and two hypotheses tested at 0.05 level of significance, guided the study. The study adopted a correlation survey. The population was senior secondary school Biology students in Onitsha Education zone of Anambra state while the sample was drawn using Taro Yamane formula for sample size determination which gave approximately 298 students (105 males and 193 females). Two instruments were used for data collection, they include; Students’ Rating of Teacher quality SRTQ adapted from Umeji (2025) and 2024/2025 performance of students from the Biology teachers grade book from the sampled schools. The Student Rating Teacher Quality SRTQ which shows a consistent reliability of 0.82 using Cronbach alpha. The data was analyzed using Pearson moment r and R2 to answer research questions and ANOVA (linear and multiple) regression to test null hypotheses at 0.05 alpha level. The findings revealed, among others, that low positive relationship exist between teacher quality and secondary school students’ performance in Biology concept of genetics. However, there is no significant relationship between teacher quality and secondary school students’ performance in Biology concept of genetics. It was concluded that low positive relationship exists between teacher quality and secondary school students’ performance in Biology concept of genetics and also there is no significant relationship between teacher quality and secondary school students’ performance in Biology concept of genetics. From the conclusion, recommendations were made.